Experimental and theoretical study on the impact of a nitrate group on the chemistry of alkoxy radicals. Issue 9 (2nd March 2021) - Novelli, A.; Cho, C.; Fuchs, H.; Hofzumahaus, A.; Rohrer, F.; Tillmann, R.; Kiendler-Scharr, A.; Wahner, A.; Vereecken, L.
Abstract : The chemistry of nitrated alkoxy radicals, and its impact on RO2 measurements using the laser induced fluorescence (LIF) technique, is examined by a combined theoretical and experimental study. Abstract : The chemistry of nitrated alkoxy radicals, and its impact on RO2 measurements using the laser induced fluorescence (LIF) technique, is examined by a combined theoretical and experimental study. Quantum chemical and theoretical kinetic calculations show that the decomposition of β-nitrate-alkoxy radicals is much slower than β-OH-substituted alkoxy radicals, and that the spontaneous fragmentation of the α-nitrate-alkyl radical product to a carbonyl product + NO2 prevents other β-substituents from efficiently reducing the energy barrier. The systematic series of calculations is summarized as an update to the structure–activity relationship (SAR) by Vereecken and Peeters (2009), and shows increasing decomposition rates with higher degrees of substitution, as in the series ethene to 2, 3-dimethyl-butene, and dominant H-migration for sufficiently large alkoxy radicals such as those formed from 1-pentene or longer alkenes. The slow decomposition allows other reactions to become competitive, including epoxidation in unsaturated nitrate-alkoxy radicals; the decomposition SAR is likewise updated for β-epoxy substituents. A set of experiments investigating the NO3 -initiated oxidation of ethene, propene, cis -2-butene, 2, 3-dimethyl-butene, 1-pentene, and trans -2-hexene, were performed in the atmospheric simulation chamber SAPHIR with measurements of HO2 and RO2 radicals performed with a LIF instrument. Comparisons between modelled and measured HO2 radicals in all experiments, performed in excess of carbon monoxide to avoid OH radical chemistry, suggest that the reaction of HO2 with β-nitrate alkylperoxy radicals has a channel forming OH and an alkoxy radical in yields of 15–65%, compatible with earlier literature data on nitrated isoprene and α-pinene radicals. Model concentrations of RO2 radicals when including the results of the theoretical calculations described here, agreed within 10% with the measured RO2 radicals for all species investigated when the alkene oxidation is dominated by NO3 radicals. The formation of NO2 in the decomposition of β-nitrate alkoxy radicals prevents detection of the parent RO2 radical in a LIF instrument, as it relies on formation of HO2 . The implications for measurements of RO2 in ambient and experimental conditions, such as for the NO3 -dominated chemistry during nighttime, is discussed. The current results appear in disagreement with an earlier indirect experimental study by Yeh et al. on pentadecene.